Search for neural correlates of object and panorama learning in mushroom body extrinsic neurons of bumblebees - Inga Fuchs; Benjamin Paffhausen; Randolf Menzel (Journal of Comparative Physiology A, 2026)
A laboratory-based setup was developed that allowed us to train bumblebees to a rewarding object (local cue) in the context of a panorama and simultaneously to record extracellularly the neural activity of units interpreted as mushroom body extrinsic neurons (MBENs). This setting simulates conditions flower visiting bees face when foraging excluding the compass related conditions. The bumblebees navigated between the colony and the test/feeding arena on their own motivation, starting from a fully functional colony with a queen. They learned by sucrose reward a specific feeding place marked by the rewarding object local cue (blue pyramid cylinder) placed in a fixed spatial relation to the panorama (matching panorama). Spontaneous choice tests and extinction tests revealed enhanced search behavior for the learned matching condition. Single or multiple (up to three) simultaneously recorded neurons referred to here as units revealed learning-related differences either by increased, decreased or unchanged neural activity. We focused on tests in which the local cue was presented in the same area as the panorama (learned condition: matched) or in separate areas (mismatched condition). Neural activity differed in these two test conditions. This learning effect did not depend on the areas tested, indicating that the whole arena had been learned as an environment in which the local cue and the panorama were spatially related. No changes in neural activity were found for head direction toward the goal (local cue, panorama, matched or mismatched), distance to the goals or the gateway. No place-cell-like activity patterns were found. Significant neural effects were also seen in some units during multiple walks between local cue and panorama in mismatch tests.

Encoding and decoding of the information in the honeybee waggle dance - Zhengwei Wang; Xiuxian Chen; Ryuichi Okada; Stefan Walter; Randolf Menzel (Behavioral Ecology and Sociobiology, 2025)
Communication processes are characterized by three components: the encoding of a message by the sender, the content of the message, and the process of decoding by the receiver. In honeybee waggle dance communication, the dancing bee encodes the vector as defined by the distance and direction of its outbound flight; the content of the message is a vector that defines a location by its endpoint in a rectangular (Cartesian) or circular diagram; and the dance follower (the recruited bee) translates (decodes) this message into search behavior. Analyses of this communication process have so far depended on the experimenter’s knowledge of the geographic location of the hive and the feeder. We applied an approach fully independent of the experimenter’s knowledge by quantifying the encoding process by video recording the dance behavior (the waggle runs) and tracking the recruits’ flights with harmonic radar. The vector code of the dancer and the search pattern of the recruits led to 2D density distributions that are embedded in the landscape. These density maps (heatmaps) of the encoding and decoding processes were compared quantitively. We found (1) a non-linear relation between the distance code (number of waggles per waggle run) and the centroid of the search, (2) the dependence of the search pattern on the landscape structure, and (3) effects of the training procedure of the dancers. Importantly, recruits search more precisely than expected from the distribution of vector endpoints as encoded in the dancers’ waggle runs. The high search precision can be modeled by assuming an averaging over eight waggle runs, but other phenomena may also be involved (systematic deviations in the vector code, structure of the landscape memory). The high precision of the recruits’ search pattern explains why previous analyses of the dance communication of bees are largely adequate.

Navigation and dance communication in honeybees: a cognitive perspective - Randolf Menzel (Journal of Comparative Physiology A, 2023)
Flying insects like the honeybee experience the world as a metric layout embedded in a compass, the time-compensated sun compass. The focus of the review lies on the properties of the landscape memory as accessible by data from radar tracking and analyses of waggle dance following. The memory formed during exploration and foraging is thought to be composed of multiple elements, the aerial pictures that associate the multitude of sensory inputs with compass directions. Arguments are presented that support retrieval and use of landscape memory not only during navigation but also during waggle dance communication. I argue that bees expect landscape features that they have learned and that are retrieved during dance communication. An intuitive model of the bee’s navigation memory is presented that assumes the picture memories form a network of geographically defined locations, nodes. The intrinsic components of the nodes, particularly their generalization process leads to binding structures, the edges. In my view, the cognitive faculties of landscape memory uncovered by these experiments are best captured by the term cognitive map.

A neural network model for familiarity and context learning during honeybee foraging flights - Jurek Müller; Martin Nawrot; Randolf Menzel; Tim Landgraf (Biological Cybernetics, 2018)

The memory structure of navigation in honeybees - Randolf Menzel; Uwe Greggers (Journal of Comparative Physiology A, 2015)

Effect of GABAergic inhibition on odorant concentration coding in mushroom body intrinsic neurons of the honeybee - Anja Froese; Paul Szyszka; Randolf Menzel (Journal of Comparative Physiology A, 2014)

Guidance by odors in honeybee navigation - Randolf Menzel; Uwe Greggers (Journal of Comparative Physiology A, 2013)

Scouts behave as streakers in honeybee swarms - Uwe Greggers; Caspar Schöning; Jacqueline Degen; Randolf Menzel (The Science of Nature, 2013)

Dominance of the odometer over serial landmark learning in honeybee navigation - Randolf Menzel; Jacqueline Fuchs; Leonard Nadler; Benjamin Weiss; Nicole Kumbischinski; Daniel Adebiyi; Sergej Hartfil; Uwe Greggers (The Science of Nature, 2010)

Innervation pattern of suboesophageal ventral unpaired median neurones in the honeybee brain - Ulrike Schröter; Dagmar Malun; Randolf Menzel (Cell and Tissue Research, 2007)

Spatial memory, navigation and dance behaviour in Apis mellifera - Randolf Menzel; Rodrigo J. De Marco; Uwe Greggers (Journal of Comparative Physiology A, 2006)

Visualizing mushroom body response to a conditioned odor in honeybees - Till Faber; Randolf Menzel (The Science of Nature, 2001)

A digital three-dimensional atlas of the honeybee antennal lobe based on optical sections acquired by confocal microscopy - C. G. Galizia; Sabrina L. McIlwrath; Randolf Menzel (Cell and Tissue Research, 1999)

Discrimination of coloured stimuli by honeybees: alternative use of achromatic and chromatic signals - Martin Giurfa; Misha Vorobyev; Robert Brandt; Britta Posner; Randolf Menzel (Journal of Comparative Physiology A, 1997)

Memory dynamics and foraging strategies of honeybees - Uwe Greggers; Randolf Menzel (Behavioral Ecology and Sociobiology, 1993)